FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN BERAT BADAN LAHIR RENDAH (Studi di Kabupaten Wonosobo, Jawa Tengah) - Wahyu Rochadi; Zinatul Faizah (Universitas Muhammadiyah Semarang, 2005)
The study was conducted or correlated to identified some factors with Low Birth Weight. Such as characteristic of mother, sosial cultur, nutrition state, health stqte, ante natal care, haemoglobin